2015
DOI: 10.1371/journal.pone.0131020
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting LTP-Like Plasticity in Human Motor Cortex by Spaced Paired Associative Stimulation

Abstract: Paired associative stimulation (PASLTP) of the human primary motor cortex (M1) can induce LTP-like plasticity by increasing corticospinal excitability beyond the stimulation period. Previous studies showed that two consecutive PASLTP protocols interact by homeostatic metaplasticity, but animal experiments provided evidence that LTP can be augmented by repeated stimulation protocols spaced by ~30min. Here we tested in twelve healthy selected PASLTP responders the possibility that LTP-like plasticity can be augm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 56 publications
3
22
1
Order By: Relevance
“…Previous studies report that plasticity is blocked following 5 minute interval spaced iTBS [20], and facilitated/prolonged with either 10 minute intervals [37] or 3 blocks of 15 minute intervals [38]. Furthermore, repeated blocks of facilitatory paired associative stimulation, another TMS paradigm which induces LTP-like plasticity, prolongs plasticity duration [39]. In contrast, several studies have reported blocking or reversal of plasticity following repeated iTBS intervals at 15 [34], 20 [20] and 25 minutes [36].…”
Section: The Duration Between Repeated Blocks Of Itbs Impacts Plasticmentioning
confidence: 99%
“…Previous studies report that plasticity is blocked following 5 minute interval spaced iTBS [20], and facilitated/prolonged with either 10 minute intervals [37] or 3 blocks of 15 minute intervals [38]. Furthermore, repeated blocks of facilitatory paired associative stimulation, another TMS paradigm which induces LTP-like plasticity, prolongs plasticity duration [39]. In contrast, several studies have reported blocking or reversal of plasticity following repeated iTBS intervals at 15 [34], 20 [20] and 25 minutes [36].…”
Section: The Duration Between Repeated Blocks Of Itbs Impacts Plasticmentioning
confidence: 99%
“…As Muller‐Dahlhaus et al . () reported homoeostatic interactions at longer IPIs in young subjects, we expected that older adults would show homoeostatic metaplasticity at the 30‐min interval. However, based on our own previous findings, we expected that metaplastic interactions would be reduced in older adults at the 10‐min interval.…”
Section: Introductionmentioning
confidence: 95%
“…In particular, a recent study in young subjects has shown that the time interval between priming and test blocks of PAS (i.e. the inter‐PAS interval; IPI) is a key factor in determining the nature of metaplastic interactions, with two consecutive sessions of PAS separated by 30 min being most effective at augmenting LTP‐like plasticity (Muller‐Dahlhaus et al ., ). It is currently unknown whether changing the interval between the priming and test NIBS interventions can augment plasticity induction in older adults, with the possibility that there is a change in the temporal dependency of metaplastic effects in the elderly.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, paired associative stimulation involving the repeated pairing of peripheral nerve stimulation and TMS over M1 operates with spiketiming-dependent plasticity (M€ uller-Dahlhaus et al, 2015), such that increases in corticospinal excitability occur when the neural spikes transmitted through the peripheral nerves and the neural activity elicited by TMS coincide temporally in the cortex (Carson and Kennedy, 2013). In the context of BMI motor rehabilitation training in which regulation of SMR-ERD is linked with sensory feedback, Hebbian (timing dependent) plasticity might strengthen the synaptic links between the compromised afferent and efferent pathways.…”
Section: Hebbian (Timing Dependent) Plasticitymentioning
confidence: 99%